Upper Gastrointestinal Endoscopy with biopsy in paediatric feeding disorders. (28th June 2021) - Robinson, Robyn; Placone, Nicholas; Katz, Mitchell; Ornelas, Elisa
Abstract: Aim: Our aim was to evaluate upper GI pathology found endoscopically among children seen in a GI feeding clinic for persistent feeding problems compared with controls. Methods: Esophagogastroduodenoscopy biopsy results were examined among two cohorts of children. The first group included 86 children evaluated in a gastroenterology feeding clinic for paediatric feeding disorders. A comparison was made with an age‐matched control group of 86 children referred for endoscopy for conditions other than disordered feeding. Results: In the feeding cohort, 57% had abnormal endoscopy biopsies. These included 30% with microscopic esophagitis and 15.1% with eosinophilic esophagitis (EoE). Among the controls, 53% had abnormal biopsies, which included 26% with microscopic esophagitis and 8% with eosinophilic esophagitis. The statistical comparison between groups included p = 0.98 for microscopic esophagitis and p = 0.15 for eosinophilic esophagitis. Conclusion: Results demonstrated similar prevalence of abnormal endoscopy biopsies and microscopic esophagitis in both groups. The incidence of eosinophilic esophagitis in the feeding group triples that of previous reports and nearly doubles controls. Our findings suggest paediatric feeding disorders which do not resolve may warrant investigation by upper endoscopy.